AN OBSERVATIONAL TEST OF THE STRESS ACCUMULATION MODEL BASED ON SEISMICITY PRECEDING THE 1992 LANDERS, CA EARTHQUAKE - Levin S.Z.; Sammis C.G.; Bowman D.D. (My University, 2006)
We test the Bowman and King [Bowman, D.D., King, G.C.P., 2001a, Accelerating seismicity and stress accumulation before large earthquakes. Geophys. Res. Lett., 28 (21), 4039-4042, Bowman, D.D., King, G.C.P., 2001b. Stress transfer and seismicity changes before large earthquakes. C. R. Acad. Sci. Paris, 333, 591-599] Stress Accumulation model by examining the evolution of seismicity rates prior to the 1992 Landers, California earthquake. The Stress Accumulation (SA) model was developed to explain observations of accelerating seismicity preceding large earthquakes. The model proposes that accelerating seismicity sequences result from the tectonic loading of large fault structures through aseismic slip in the elasto-plastic lower crust. This loading progressively increases the stress on smaller faults within a critical region around the main structure, thereby causing the observed acceleration of precursory activity. A secondary prediction of the SA model is that the precursory seismicity rates should increase first at the edges of the critical region, with the rates gradually rising over time at closer distances to the main fault. We test this prediction by examining year-long seismicity rates between 1960 and 2004, as a function of distance from the Landers rupture. To quantify the significance of trends in the seismicity rates, we auto-correlate the data, using a range of spatial and temporal lags. We find weak evidence for increased seismicity rates propagating towards the Landers rupture, but cannot conclusively distinguish these results from those obtained for a random earthquake catalog. However, we find a strong indication of periodicity in the rate fluctuations, as well as high correlation between activity 130-170 km from Landers and seismicity rates within 50 km of the Landers rupture temporally offset 1.5-2 years. The implications of this spatio-temporal correlation will be addressed in future studies. © 2005 Elsevier B.V. All rights reserved.
Keywords: ACCELERATING MOMENT RELEASE; LANDERS; SEISMICITY RATES; STRESS ACCUMULATION